Perancangan Aplikasi Smart Zonasi Berbasis Location Based Service (LBS) SMAN di Kota Depok - Rheza Andika; Diana Ikasari; Widiastuti Widiastuti (UM Purwokerto Press, 2021)
The principle of the zoning system, which regulates regional zones for prospective students, is to bring the student's domicile closer to the school, where zoning is determined at every level by the Regional Government following its authority. In implementing zoning, it is important to pay attention to the amount of available capacity according to the availability of the number of school-age children at each level in the area. Depok City has 13 public high schools spread over 11 sub-districts that can accommodate 3,858 junior high school graduates. This became disproportionate to the number of outputs or junior high school graduates who were more than the available capacity. Based on the use of LBS technology, it was hoped that it would be easier to obtain information on the distance from the user's domicile to the destination school, where in the Depok there are 13 State Senior High Schools that are the reference. In designing the Location Based Services (LBS) application, SMAN Depok City used case diagrams, navigation structure designs, storyboards and database designs. The page design and database design results were expected to be used as a guide for programmers in making applications.